2009
DOI: 10.1016/j.expneurol.2008.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor-enhanced neurogenesis contributes to cognitive recovery in rats following traumatic brain injury

Abstract: Stem/progenitor cells reside throughout the adult CNS and are actively dividing in the subventricular zone (SVZ) and the dentate gyrus (DG) of the hippocampus. This neurogenic capacity of the SVZ and DG is enhanced following traumatic brain injury (TBI) suggesting that the adult brain has the inherent potential to restore populations lost to injury. This raises the possibility of developing strategies aimed at harnessing the neurogenic capacity of these regions to repair the damaged brain. One strategy is to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
1
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 61 publications
2
115
1
3
Order By: Relevance
“…Because neither study examined neuroprotection within the dentate gyrus, it is possible that the cognitive improvements accompanying FGF-2 administration were related to a reduction in cell death or enhancement of neurogenesis within the dentate. In a 2009 study, Sun et al [114] demonstrated enhanced post-traumatic neurogenesis in the hippocampus and SVZ using a FGF-2 treatment paradigm that also improved cognitive function after TBI in rats. Similarly, overexpression of FGF-2 in hippocampal cells achieved through stereotactic injection of FGF-2 expressing viral vectors enhanced neurogenesis and reduced granule cell layer cell loss in mice after CCI brain injury [110].…”
Section: Fgf-2mentioning
confidence: 99%
“…Because neither study examined neuroprotection within the dentate gyrus, it is possible that the cognitive improvements accompanying FGF-2 administration were related to a reduction in cell death or enhancement of neurogenesis within the dentate. In a 2009 study, Sun et al [114] demonstrated enhanced post-traumatic neurogenesis in the hippocampus and SVZ using a FGF-2 treatment paradigm that also improved cognitive function after TBI in rats. Similarly, overexpression of FGF-2 in hippocampal cells achieved through stereotactic injection of FGF-2 expressing viral vectors enhanced neurogenesis and reduced granule cell layer cell loss in mice after CCI brain injury [110].…”
Section: Fgf-2mentioning
confidence: 99%
“…However, several studies have examined the effect of administering neurogenic agents to rodent models of TBI to assess the effect on neuronal replacement and functional recovery. Administration of EGF or FGF-2 into the lateral ventricles following FPI has been shown to increase the rate of memory recovery in the Morris Water Maze, and produce a concomitant increase in the number of new hippocampal neurons co-labeled with BrdU and NeuN (Sun, et al, 2009, Sun, et al, 2010. Interestingly, intraventricular administration of the calcium-binding protein S100 following TBI has also been shown to increase the percentage of newly generated hippocampal neurons expressing NeuN and improve cognitive recovery in the Morris water Maze [for review see (Kleindienst, et al, 2007)].…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…The optical fractionator method was used to estimate the total number of BrdU-positive cells following our previously described method (Sun et al, 2009). This design-based stereological method to estimate cell numbers has been widely used by our lab.…”
Section: Stereological Quantification Of Brdu-labeled Transplanted Cellsmentioning
confidence: 99%
“…To estimate the total number of transplanted BrdU-labeled cells that were present at 2 or 4 weeks after injection, six 50-lm-thick coronal sections through the injection site spaced 300 lm apart were quantified using an unbiased stereological optical fractionator method as previously described (Sun et al, 2009. A total of 8 · 10 4 cells (4 · 10 4 · 2 lL) were injected initially.…”
Section: Survival Of Transplanted Adult Rat Ns/npcsmentioning
confidence: 99%